RB ISOTOPE DILUTION ANALYSES BY MC-ICPMS USING ZR TO CORRECT FOR MASS FRACTIONATION: TOWARDS IMPROVED RB-SR GEOCHRONOLOGY? - Waight T.; Baker J.; Willigers B. (My University, 2002)
A new technique is presented where mass fractionation during Rb isotope dilution analyses by multi-collector inductively coupled plasma mass spectrometry is corrected for by measuring the amount of fractionation on admixed Zr. Replicate analyses of natural Rb interspersed with analyses of 87Rb tracer enriched samples yield a mean 87Rb/85Rb=0.38540±19 (0.05%, 2 s.d.), assuming a natural 90Zr/91Zr of 4.588. Each Rb analysis takes 1 min, consumes 20 ng of Rb and has an internal precision of ∼0.02% (2 s.e.). Washouts between samples take 5 min. Persistent but small stable Rb backgrounds are overcome by an on-peak-zeroes (OPZ) measurement prior to data acquisition. Close examination of measured 87Rb/85Rb and 90Zr/91Zr ratios indicate small changes in relative fractionation of Rb and Zr during plasma ionisation occur when different sample introduction techniques are used (e.g., ‘wet’ vs. ‘dry’ nebulisation), although the differences are insignificant compared to the level of precision required for isotope dilution measurements. Replicate analyses of whole rock samples suggest a reproducibility for Rb concentration measurements of ≤0.5% and 87Rb/86Sr measurements of 0.2% when interfering Sr is reduced to satisfactory levels. However, it is difficult to ascertain to what extent this reproducibility reflects the limit of the technique or powder heterogeneity. Much of the error involved in the Rb isotope dilution and Sr isotope ratio measurements by multiple collector inductively coupled plasma mass spectrometry (MC-ICPMS) is derived from uncertainties as to which 87Sr/86Sr (and 87Rb/85Rb) ratios to use when correcting for isobaric interferences due to the presence of spike Sr and Rb at mass 87. If isobaric interferences are minimised by efficient separation of Rb from Sr during cation exchange chemistry, the use of natural ratios for isobaric interference corrections yields the most reproducible data, indicating that the interferences are derived from environmental blank. Larger isobaric interferences at mass 87 are indicative of inefficient chemical separations, and the measured ratio from the complementary analysis provide more reproducible data. Burning off of Rb during conventional thermal ionisation mass spectrometry (TIMS) Sr isotope analysis nullifies this isobaric interference, and therefore, TIMS remains the method of choice for reliable and precise 87Sr/86Sr determinations on spiked samples. Application of our technique to minerals separated from Tertiary to Palaeozoic plutons yields age data consistent with previous determinations. Where different two-point isochron ages can be calculated for individual plutons, the ages reproduce to ≤±0.3%. The method represents an initial improvement in Rb isotope dilution measurements over TIMS by allowing a quantifiable correction to be made for mass fractionation, confirmed by duplicate analyses of standards and samples by both TIMS and MC-ICPMS. Mass fractionation corrected Rb isotope dilution analyses should result in: (1) improved Rb–Sr geochronology in examples where the Rb–Sr ratio provides the largest source of error; (2) application of this improved method to Rb–Sr geochronology on smaller samples such as single mica-flakes and micro-drill samples and; (3) by comparison with other geochronological techniques, more detailed cooling and crystallisation histories of igneous and metamorphic rocks. Taking advantage of these improvements requires a reevaluation of the Rb decay constant, which this technique should also permit.